2022
DOI: 10.3201/eid2807.211528
|View full text |Cite
|
Sign up to set email alerts
|

One Health Genomic Analysis of Extended-Spectrum β-Lactamase‒Producing Salmonella enterica, Canada, 2012‒2016

Abstract: N ontyphoidal Salmonella is a leading cause of foodborne diarrheal illness. There were an estimated 535,000 human cases of invasive infection with nontyphoidal Salmonella and 59,100 deaths in 2017 globally (1,2). Gastroenteritis is usually self-limiting, but antimicrobial treatment, including ceftriaxone, ciprofloxacin, trimethoprim/sulfamethoxazole, or amoxicillin, might be recommended for severe disease and invasive infections (3).Extended-spectrum cephalosporins are a major class of broad-spectrum antimicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…Nor did the plasmid replicons have any similarity to what was detected in Shigella , because the IncHI2 plasmid replicon (10/31) was most prevalent in Salmonella (Table S6). Previous studies have shown a wide range of possible plasmid replicons in Salmonella in other countries, such as IncHI2, IncA/C, IncL/M, IncI1, IncF, IncK and IncN plasmid replicons, with IncA/I occurring both in humans and in animals [74–76]. Prediction tools showed that in Salmonella probably all ESBL genes were localized on plasmids, but only for isolate i104 was the ESBL gene on the same contig as the plasmid replicon.…”
Section: Resultsmentioning
confidence: 99%
“…Nor did the plasmid replicons have any similarity to what was detected in Shigella , because the IncHI2 plasmid replicon (10/31) was most prevalent in Salmonella (Table S6). Previous studies have shown a wide range of possible plasmid replicons in Salmonella in other countries, such as IncHI2, IncA/C, IncL/M, IncI1, IncF, IncK and IncN plasmid replicons, with IncA/I occurring both in humans and in animals [74–76]. Prediction tools showed that in Salmonella probably all ESBL genes were localized on plasmids, but only for isolate i104 was the ESBL gene on the same contig as the plasmid replicon.…”
Section: Resultsmentioning
confidence: 99%
“…Both clinical and environmental non‐O1/O139 populations of V. cholera were reported to be related to a cholera outbreak in 2010 in Haiti, based on whole‐genome sequencing data (Hasan et al., 2012 ). In contrast, low phylogenetic similarity was observed between Canadian human and animal extended‐spectrum β‐lactamases‐producing Salmonella (Bharat et al., 2022 ). In the future, using the methods described here, the source of disease outbreaks could be identified.…”
Section: Discussionmentioning
confidence: 99%
“…В нашем исследовании частота встречаемости НТС продуцентов БЛРС и AmpC составляла 1,45% (n = 26), среди которых 22 штамма содержали различные blaгены молекулярных классов А и D (bla TEM , bla CTXM , bla SHV , bla OXA ), 1 штамм -AmpC (bla CMY2 ) и 3 штаммакомбинацию БЛРС класса А и AmpC (bla TEM , bla CMY2 , bla DHA ) (Таблица 1). Частота выявления БЛРС и AmpC продуцирующих сальмонелл в зависимости от источника выделения составляла 1,54% от человека (общее количе ство исследованных изолятов, n = 1037), 1,8% -из про дуктов питания (от n = 499) и 0,39% -из внешней среды (от n = 257), что намного превышает значения, получен ные в результате исследования в Канаде [33], где в тече ние 2012-2016 гг. частота выявления составляла 0,35% от людей и 0,31% от животных/мяса.…”
Section: Discussionunclassified